2015
DOI: 10.1016/j.crme.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The permeability and quality of velocity field in a square array of solid and permeable cylindrical obstacles with the TRT–LBM and FEM Brinkman schemes

Abstract: Available online xxxx Keywords: Brinkman equation Bimodal porous flow system Lattice Boltzmann equation TRT Brinkman model Finite element Galerkin methodUsing as a benchmark the porous flow in a square array of solid or permeable cylindrical obstacles, we evaluate the numerical performance of the two-relaxation-time lattice Boltzmann method (TRT-LBM) and the linear finite element method (FEM). We analyze the bulk, boundary and interface properties of the Brinkman-based schemes in staircase discretization on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
(114 reference statements)
1
9
0
Order By: Relevance
“…[56], confirms that the IBF effectively suppresses strong interface fluctuations typical in BF and FEM. The random and bimodal two-dimensional benchmarks are of the special interest in this context, since they provide nontrivial validation to scheme (54), which has been derived for the straight channel.…”
Section: Discussionsupporting
confidence: 64%
“…[56], confirms that the IBF effectively suppresses strong interface fluctuations typical in BF and FEM. The random and bimodal two-dimensional benchmarks are of the special interest in this context, since they provide nontrivial validation to scheme (54), which has been derived for the straight channel.…”
Section: Discussionsupporting
confidence: 64%
“…At the same time, the FEM simulation of Brinkman flows has also found vast application (Krotkiewski et al 2011;Hannukainen et al 2011). A detailed comparison on the specificities of both numerical approaches in this class of problems was performed in the recent works Silva and Ginzburg 2015). The most evident difference between them is that the FEM explicitly prescribes exact continuity conditions for velocity and stress components (with effective viscosity) on the vertex-centred grid, while the LBM imposes them implicitly and approximately in-between the centres of grid cells.…”
Section: Numerical Evaluationmentioning
confidence: 99%
“…This section makes use of numerical simulations validated at sufficiently fine grids for the parameter range studied Silva and Ginzburg 2015), which allows one to evaluate the applicability/limitations of the cell model and lubrication theory solutions.…”
Section: Numerical Evaluationmentioning
confidence: 99%
“…(8) , even when Error (II) is absent due to A = 0 , the removal of Error (I) will require = 3 / 8 for this setup. Worse, the studies [32][33][34] have identified this problem and showed that Error (I), which is intrinsic to the LBM discretization of non-uniform body forces, gets transferred from bulk to boundaries; for example, in the BB case it leads to body force -dependent artefacts that affect the precision of the no-slip wall location on a much larger extent, at both O(δx ) and O(δx 2 ) (i.e. they affect the BB accommodation of both the flow gradient and the flow curvature).…”
Section: A Note On the Effect Of The Lbm Force Errors On Boundariesmentioning
confidence: 99%
“…they affect the BB accommodation of both the flow gradient and the flow curvature). This implies that, in this case, there is no single value capable of fixing the BB wall location at the desired place; for a detailed discussion on the pros and cons of using = 3 / 16 vs. = 3 / 8 in the BB wall modeling of this problem class we refer to [32][33][34] .…”
Section: A Note On the Effect Of The Lbm Force Errors On Boundariesmentioning
confidence: 99%